Community training in dishwashing-liquid soap making from waste cooking oil - Evelyn Evelyn; Edy Saputra; Komalasari Komalasari; Syelvia Putri Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Cooking oil that has been used more than once is not good for health due to exposure to carcinogens. Waste cooking oil causes pollution to the environment. Waste cooking oil can be used as a raw material for making liquid soap. The objective of this activity was to introduce the knowledge and train Batu Basurat community in making dishwashing-liquid soap from waste cooking oil. The method consists of location survey, training preparation, interactive training, monitoring, and evaluation. Dishwashing-liquid soap was made by mixing preheated waste cooking oil and potassium hydroxide (KOH) at 60-70 °C for one hour until trace was formed. Then, the mixture was kept agitated every 15 minutes for 2-3 hours until it becomes more solidified and transparent. Liquid soap was made by dissolving in warm water and addition of lemon essence as a deodorizer. Batu Basurat villagers showed a great interest in the activity, showing by enthusiasm and involvement in the training. Evaluation results showed that 100% community understood on making homemade dishwashing-liquid soap and 90% community agreed that liquid soap from waste cooking oil has a commercial potential, which could increase entrepreneurship ability and economic growth of Batu Bersurat villagers.